Effect of cultural conditions on antimicrobial activity of marine-derived fungus Penicillium chrysogenum - Trinh, Phan Thi Hoai; Ngoc, Ngo Thi Duy; Tien, Phi Quyet; Ly, Bui Minh; Van, Tran Thi Thanh (Vietnam Journal of Biotechnology, 2018)
Marine fungi are a potential source of structurally diversified bioactive secondary metabolites that are not found in terrestrial sources. In our continuous investigation to search new antimicrobial agents from marine-derived fungi, we isolated fungal strain 045-357-2 from a soft coral sample collected from Ca Na bay, Ninh Thuan, Vietnam. The strain showed high antibacterial activity and was selected for further study. According to Internal Transcribed Spacer (ITS) rDNA molecular methods, the fungus was identified as Penicillium chrysogenum 045-357-2 and had a 100% homology (600/600 bp) with a GenBank sequence from a reference P. chrysogenum strain (NCBI accession no. EF200090). In the present investigation, the fungus was studied on effect of different culture incubation period, pH and salinity for antimicrobial activity against pathogenic microbes including Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus cereus, Streptococcus faecalis, Listeria monocytogenes, and Candida albicans. The ethyl acetate extracts of culture medium of the fungal isolate were determined antimicrobial activity by disc diffusion assay. The results showed that the optimum antimicrobial activity of the fungal strain P. chrysogenum 045-357-2 was obtained in medium containing 20 g rice, 20 mg yeast extract, 10 mg KH2PO4 , and 40 mL natural seawater at 30oC on the 14th day of incubation. The strain also exhibited highest antimicrobial activity in the medium at initial pH 6.0 – 8.0 and salinity of 35 g/L. The findings indicate that cultural conditions significantly influenced on antimicrobial activity of the studied fungus. The optimization is potential use for further study on the mass cultivation and isolation of bioactive compounds for this fungus